ANGPTL8 protein-truncating variant associated with lower serum triglycerides and risk of coronary disease - Helkkula, Pyry; Kiiskinen, Tuomo; Havulinna, Aki S.; Karjalainen, Juha; Koskinen, Seppo; Salomaa, Veikko; Daly, Mark J.; Palotie, Aarno; Surakka, Ida; Ripatti, Samuli (PLoS genetics, 2021)
Protein-truncating variants (PTVs) affecting dyslipidemia risk may point to therapeutic targets for cardiometabolic disease. Our objective was to identify PTVs that were associated with both lipid levels and the risk of coronary artery disease (CAD) or type 2 diabetes (T2D) and assess their possible associations with risks of other diseases. To achieve this aim, we leveraged the enrichment of PTVs in the Finnish population and tested the association of low-frequency PTVs in 1,209 genes with serum lipid levels in the Finrisk Study (n = 23,435). We then tested which of the lipid-associated PTVs were also associated with the risks of T2D or CAD, as well as 2,683 disease endpoints curated in the FinnGen Study (n = 218,792). Two PTVs were associated with both lipid levels and the risk of CAD or T2D: triglyceride-lowering variants in ANGPTL8 (-24.0[-30.4 to -16.9] mg/dL per rs760351239-T allele, P = 3.4 × 10 −9 ) and ANGPTL4 (-14.4[-18.6 to -9.8] mg/dL per rs746226153-G allele, P = 4.3 × 10 −9 ). The risk of T2D was lower in carriers of the ANGPTL4 PTV (OR = 0.70[0.60–0.81], P = 2.2 × 10 −6 ) than noncarriers. The odds of CAD were 47% lower in carriers of a PTV in ANGPTL8 (OR = 0.53[0.37–0.76], P = 4.5 × 10 −4 ) than noncarriers. Finally, the phenome-wide scan of the ANGPTL8 PTV showed that the ANGPTL8 PTV carriers were less likely to use statin therapy (68,782 cases, OR = 0.52[0.40–0.68], P = 1.7 × 10 −6 ) compared to noncarriers. Our findings provide genetic evidence of potential long-term efficacy and safety of therapeutic targeting of dyslipidemias.